PMarketing in Consumer Interest Attracting Strategy Reviewed from Islamic Business Ethics (Case Study on Meatball and Chicken Noodle Traders in Purnama Larangan Luar Village) - Sajidah; Abdur Rohman (ORGANIZE: Journal of Economics, Management and Finance, 2024)
This study aims to examine how the application of Islamic business ethics in marketing strategies can affect consumer interest, with a case study on Bakso and Mie Ayam Purnama traders in Larangan Luar Village. The Islamic business ethics approach includes the principles of honesty in promotion, fairness in pricing, trustworthiness in service, avoidance of usury and fraud, social and environmental benefits, and openness to criticism and suggestions (ihtisab). The results show that traders who consistently apply the principles of Islamic business ethics can increase consumer trust, satisfaction, and loyalty. Honesty in promotion and transparency of information help build trust, while fair pricing creates customer satisfaction. Trustworthy and quality service provides a positive experience for consumers, and openness to criticism and suggestions strengthens the relationship between merchants and consumers. Overall, the application of Islamic business ethics in marketing strategies proved to be effective in attracting consumers and improving business reputation in the eyes of the community. This study also provides recommendations for merchants to continue developing ethical and sustainable marketing strategies, as well as suggestions for further research in expanding the understanding of the impact of Islamic business ethics in various business contexts.